Adaptive, but not condition-dependent, body shape differences contribute to assortative mating preferences during ecological speciation. (1st December 2016) - Greenway, Ryan; Drexler, Shannon; Arias-Rodriguez, Lenin; Tobler, Michael
Abstract: Assortative mating is critical for reproductive isolation during speciation; however, the mechanisms underlying mating preferences are often unknown. Assortative mating can be mediated through preferences for condition-dependent and adaptive ("magic") traits, but rigorously testing these hypotheses has been impeded by trait covariation in living organisms. We used computer-generated models to examine the role of body shape in producing association preferences between fish populations undergoing ecological speciation in different habitat types. We demonstrate that body shape can serve as an adaptive trait (variation in head size between populations) and a condition-dependent signal (variation in abdominal distention among individuals). Female preferences for stimuli varying in only one aspect of body shape uncovered evidence for body shape as a magic trait across population pairs, but no evidence for body shape serving as a condition-dependent signal. Evolution of preferences only in females from one habitat type as well as stronger preferences in sympatric nonsulfidic as opposed to allopatric nonsulfidic populations suggests that reinforcement may have played a role in producing the observed patterns.